Successful Aging Among Community-Dwelling Older Adults in Rural Areas of Jember District - Amalda, Adela Hery Prasilia; Kurdi, Fahruddin; Susumaningrum, Latifa Aini (Al-Hijrah Indonesia, 2024)
Background: Successful aging is a condition when the elderly not only live long but remain in good health so that they can be independent, and useful. Purpose: This study aims to determine the description of successful aging in the elderly at Karang Werda, Rambipuji District, Jember Regency. Methods: This study used a descriptive observational design with a cross-sectional approach and involved 213 elderly people selected by total sampling. The research instrument used the Successful Aging Scale (SAS). Data analysis used descriptive statistical tests and a chi-square test in crosstab analysis to analyze the characteristics of respondents with successful aging. Results: The success rate of aging in the elderly was mostly high. The highest indicators of successful aging were primary and secondary control, while the lowest were selection optimization and compensation. Analysis showed associations between the characteristics of age, gender, education, and smoking habits with successful aging (p-value < 0.05), while marital status, medical history, living status, employment, and income were not associated (p-value > 0.05). Conclusion: The majority of the elderly in Karang Werda, Rambipuji District, Jember Regency, showed a high level of successful aging.